The mechanism of delaying starch digestion by luteolin. Issue 23 (4th November 2021) - Zhao, Yiling; Wang, Ming; Zhang, Jinsheng; Xiong, Chunhong; Huang, Ganhui
Abstract : The mechanisms of luteolin delaying starch digestion by two methods, inhibiting α-amylase and binding with starch directly, were studied. Abstract : In this study, the mechanisms of the delay of starch digestion by luteolin were revealed by studying the luteolin–PPA (porcine pancreatic α-amylase) interaction and luteolin–starch interaction. The luteolin–PPA interaction was investigated by inhibitory kinetics analysis, fluorescence quenching, circular dichroism (CD), Fourier transform infrared (FT-IR) spectroscopy and molecular docking. The results of the inhibitory kinetics revealed that luteolin was a mixed-type inhibitor of PPA and that the inhibitory action was reversible. Fluorescence spectroscopy (including fluorescence quenching and thermodynamics) and molecular docking analyses indicated that hydrogen bonds and hydrophobic forces were the main forces between PPA and luteolin. CD and FT-IR spectroscopy analyses showed that the interaction between luteolin and PPA changed the secondary structure of PPA and induced a decline in its activity. In addition, the luteolin–starch interaction was also studied using UV–visible absorption and X-ray diffraction analyses. These indicated that luteolin could bind with PPA, and that hydrogen bonds and van der Waals forces may be present. Overall, luteolin delayed starch digestion not only by binding with PPA but also by binding with starch. Thus, luteolin has the potential to prevent and control diabetes by being added into starch-based food to delay starch digestion.